Hegels Betrachtung ständischer Privilegien - Rosanovich, Damian Jorge (2017)
The purpose of this paper is to clarify Hegel’s interpretation of political privileges. We irst analyze the place, function, and the signiicance of these leges speciales in which context Hegel explains his theory, particularly, in the Allgemeines Landrecht für die Preußischen Staaten and in the discussion concerning the Württemberg Constitution in 1815/16. We then explain Hegel’s objection to these prerogatives, which are defended in the aforementioned contexts by the privileged classes: (i) class privileges are oriented against the State; (ii) these exclusive rights are incompatible with the idea of an organic ethical life and the ethical basis of citizenship; (iii) these prerogatives obstruct the unity of the State by jeopardizing the political order in front of a revolution. Furthermore, we evaluate the manner in which Hegel manages to reconsider the concept of ‘Privileg’, from the perspective of the division of the State to the integration and the articulation of the body politic by the inner division of the branches of labor in Civil Society. The Hegelian privileges form the nervations presented in the mediations between individuals and State i.e. classes and corporations. In order to overcome the dilemma between the Monarch and the Assembly of Estates, Hegel modiies the meaning of the idea of privileges. They have to be instances which articulate the different elements between individuals and State, but they cannot be special rights against the State.